Antioxidant Activities, Total Phenolic Compounds and Fucoxanthin of Marine Benthic Diatoms Amphora subtropica BUUC1502 and Thalassiosira sp. - Setthamongkol, Pakawan; Siranonthana, Nisa; Chalermmueang, Ranchayanee; Yuyen, Yutthaya; Watanachote, Janjarus; Hiransuchalert, Rachanimuk; Kutako, Maliwan (Journal of Food Health and Bioenvironmental Science, 2023)
This research’s aim was to study antioxidant activities, total phenolic compounds and fucoxanthin of crude extract of marine benthic diatoms, Amphora subtropica BUUC1502 and Thalassiosira sp. These two diatoms were cultured in a Guillard F/2 media, which was prepared from sea water with a salinity at 30 psu for 8 days. It was found that A. subtropica BUUC1502 shows better growth than Thalassiosira sp. (p<0.05). Whereas the biomass yield of Thalassiosira sp. is higher than of A. subtropica BUUC1502 (p<0.05). The diatoms were extracted using methanol solvent (99.8%). Crude extracts of A. subtropica BUUC1502 and Thalassiosira sp. yielded 0.38±0.01 and 0.36±0.00 g/g DW, respectively. The total phenolic compounds and fucoxanthin of them were similar (p>0.05) with 2.92-3.09 mg GAE/g crude extract and 18.85-19.74 mg/g DW, respectively. The IC50 of DPPH free radical inhibition of crude extracts from A. subtropica BUUC1502 and Thalassiosira sp. is 231.75±40.75 and 179.84±27.90 µg/mL, respectively, while the IC 50 of ABTS free radical inhibition is 68.28±7.31 and 46.90±1.83 µg/mL, respectively. The results of this research show that these two marine benthic diatoms may be an antioxidant source that can be used in various related fields.